Penerapan Digital Marketing Sebagai Upaya Dalam Meningkatkan Volume Penjualan Produk Batik Oleh CV. Wecono Asri Kediri - Saputro, Rizki; Suwarsono, Bambang; Muttaqien, Zaenul (Jurnal Cendekia Manajemen (JCM); Vol 2 No 1 (2024): March, 2024)
Digital marketing is a transformation in marketing activities that can change how business people develop the business they run. The purpose of this study is to find out how CV. Wecono Asri Kediri implements digital marketing, whether by implementing digital marketing CV sales volume. Wecono Asri Kediri can improve, what are the obstacles and how to overcome the obstacles faced by CV. Wecono Asri Kediri in implementing digital marketing. This research uses qualitative descriptive method with case study approach. Data collection techniques by observation, interviews, documentation, literature studies. Data analysis techniques use data reduction, data presentation, conclusion drawing and verification. Checking data validity through source triangulation, engineering triangulation. The results of this study show that CV. Wecono Asri Kediri does digital-based marketing through Instagram, WhatsApp, Tiktok. The proceeds of batik sales by CV. Wecono Asri in 2023 will experience a very high increase with total sales of Rp. 48,320,000.